2021
DOI: 10.1186/s12939-020-01358-2
|View full text |Cite
|
Sign up to set email alerts
|

Trends in out of pocket payments and catastrophic health expenditure in the Kyrgyz Republic post “Manas Taalimi” and “Den Sooluk” health reforms, 2012–2018

Abstract: Background Over the years, the Kyrgyz Republic has implemented health reforms that target health financing with the aim of removing financial barriers to healthcare including out-of-pocket health payments (OOPPs). This study examines the trends in OOPPs, and the incidence of catastrophic health expenditure (CHE) post the “Manas Taalimi” and “Den Sooluk” health reforms. Methods We used data from the Kyrgyzstan Integrated Household Surveys (2012–2018… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
0
0
Order By: Relevance
“…This might be due to the fact that single individuals do not have either spouse or family members to support financially for healthcare, or because single people tend to be physically and mentally less healthy due to less social support from the spouse and family, thus increasing their expenditures for health. This result is in line with studies which showed single unmarried respondents have higher CHE (25,(32)(33)(34) and different from studies which showed married households were more likely to incur CHE (35)(36)(37).…”
Section: Discussionsupporting
confidence: 81%
“…This might be due to the fact that single individuals do not have either spouse or family members to support financially for healthcare, or because single people tend to be physically and mentally less healthy due to less social support from the spouse and family, thus increasing their expenditures for health. This result is in line with studies which showed single unmarried respondents have higher CHE (25,(32)(33)(34) and different from studies which showed married households were more likely to incur CHE (35)(36)(37).…”
Section: Discussionsupporting
confidence: 81%